Neurological disorders and violence: a systematic review and meta-analysis with a focus on epilepsy and traumatic brain injury. - Fazel, S; Philipson, J; Gardiner, L; Merritt, R; Grann, M (2009)
The objectives of this study were to systematically review and meta-analyze the research literature on the association of common neurological disorders and violence. Keywords relating to neurological disorders and violence were searched between 1966 and August 2008. Case-control and cohort studies were selected. Odds ratios of violence risk in particular disorders compared with controls were combined using fixed-effects meta-analysis with the data presented in forest plots. Sensitivity analyses were conducted to identify possible differences in risk estimates across surveys. Information on risk factors for violence was extracted if replicated in more than one study. Nine studies were identified that compared the risk of violence in epilepsy or traumatic brain injury compared with unaffected controls. For the epilepsy studies, the overall pooled odds ratio for violent outcomes was 0.67 [95% confidence interval (CI) 0.46-0.96]. For traumatic brain injury, the odds ratio was 1.66 (95% CI 1.12-2.31). An additional 11 case-control studies investigated factors associated with violence in epilepsy and traumatic brain injury. It was not possible to meta-analyze these data. Comorbid psychopathology was associated with violence. Data on other neurological conditions was limited and unreplicated. In conclusion, although the evidence was limited and methodological quality varied, epilepsy and traumatic brain injury appeared to differ in their risk of violence compared with control populations. Longitudinal studies are required to replicate this review's provisional findings that epilepsy is inversely associated with violence and that brain injury modestly increases the risk, and further research is needed to provide information on a broader range of risk factors.